Accuracy of the Simplified Criteria for Autoimmune Hepatitis in Children: Systematic Review and Decision Analysis - Arcos-Machancoses, José V. (J Clin Exp Hepatol, 2019)
BACKGROUND/OBJECTIVES: Several studies have been conducted on the accuracy of simplified criteria for autoimmune hepatitis that were presented in 2008 as an alternative to original criteria. Our purpose is to summarize the evidence available regarding their accuracy in children and to carry out a basic clinical decision analysis based on it. METHODS: Electronic and manual searches were performed with keywords related to diagnostic validity terms. Data from included studies were extracted, and summary estimates of accuracy measures were calculated. An effect model was chosen depending on heterogeneity, and the presence of publication bias was also studied. Therapeutic threshold was calculated based on the already published data. Through a Bayesian approach, simplified criteria's clinical utility was simulated, taking into account the meta-analyzed indicators and several assumptions on the prevalence of autoimmune hepatitis. RESULTS: The search yielded 166 studies, four of which were finally included, providing a total population of 437 patients. Pooled sensitivity and specificity of the simplified criteria for the diagnosis of autoimmune hepatitis in children was 77% and 95%, respectively, with a diagnostic odds ratio of 67. No evidence of publication bias was found. For prevalences ranging from 8.5 to 85.7, the predictive value of either a positive or a negative result moved beyond the therapeutic threshold (estimated at 56%). CONCLUSIONS: The simplified criteria show high specificity and moderate sensitivity for the diagnosis of autoimmune hepatitis in children. A positive result can justify starting a therapeutic assay, but a negative result does not seem sufficient to rule out this condition.